Colliding public health priorities: A call to improve the understanding of autistic individuals utilizing housing assistance. - Lindsay Shea; Anne Roux; Amy Blank Wilson; Jonas Ventimiglia; Conner Carlton; Wei-Lin Lee; Dylan Cooper; Shelby Frisbie (PLoS ONE)
The objective of this study was to identify utilization of housing support provided by the U.S. Department of Housing and Urban Development (HUD) among autistic people in the U.S. Using 2008 and 2016 Medicaid data, we identified autistic individuals birth to 61 years and linked them to national HUD data. We characterized demographics, co-occurring conditions, and HUD program involvement. Autistic Medicaid enrollees enrolled in HUD increased by 70% between 2008 and 2016. Among 846,350 autistic Medicaid enrollees in 2016, 10.4% (n = 88,315) were HUD-assisted. HUD-assisted autistic individuals, versus non-HUD-assisted, were more likely to be Black/African American and less likely to have private insurance. Most lived in urban areas and were enrolled in the Housing Choice Voucher program. Approximately 2,600 autistic individuals (3%) were homeless at HUD entry. Growing numbers of HUD-assisted autistic individuals point toward an urgent need for federal data to understand and address public health contexts of housing affordability and instability to complement existing clinical autism research investments. Integrated public health, housing, and disability supports must address equitable income supports and housing assistance needed to support the health needs of autistic individuals.